PROFILE OF FAMILY FUNCTIONING AMONG EARTHQUAKE SURVIVORS IN PIDIE JAYA REGENCY - Julianto Julianto; Fatmawati Fatmawati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2019)
One of the important aspects of a healthy family is the apparent division of roles or functions in which the function is embedded in a harmonious hierarchical structure, and there is also a commitment to the implementation of the function. However, effective family functioning can be shaken by a number of factors, including environmental changes, such as natural disasters. Therefore, this study aimed to see the description of family functioning among earthquake survivors in Pidie Jaya Regency. The subjects taken were 30 couples (60 people), consisting of 30 husbands and 30 wives. Data collection technique was done by using Family Functioning Scale developed by Maryam (2007) by referring to Rice’s theory (1986). The results showed that most of the family members had instrumental and expressive function with medium category, with amount of 53.3% and 91.7%, respectively. This meant, family functions can run well in complete family typology.Keywords: earthquake disaster, family functioning, instrumental function, expressive function